2016
DOI: 10.1051/0004-6361/201628111
|View full text |Cite
|
Sign up to set email alerts
|

Relation between trees of fragmenting granules and supergranulation evolution

Abstract: Context. The determination of the underlying mechanisms of the magnetic elements diffusion over the solar surface is still a challenge. Understanding the formation and evolution of the solar network (NE) is a challenge, because it provides a magnetic flux over the solar surface comparable to the flux of active regions at solar maximum. Aims. We investigate the structure and evolution of interior cells of solar supergranulation. From Hinode observations, we explore the motions on solar surface at high spatial a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 24 publications
5
49
0
Order By: Relevance
“…This ring of higher cork density stands out more clearly than for the observed magnetic field. The observed network field is stronger on the west side of the average supergranule than on the east side, as we detected in our previous study (Langfellner et al 2015a) and as was later also found by Roudier et al (2016). This observation is successfully reproduced by the cork simulation (run #5).…”
Section: Cork Simulationsupporting
confidence: 88%
See 1 more Smart Citation
“…This ring of higher cork density stands out more clearly than for the observed magnetic field. The observed network field is stronger on the west side of the average supergranule than on the east side, as we detected in our previous study (Langfellner et al 2015a) and as was later also found by Roudier et al (2016). This observation is successfully reproduced by the cork simulation (run #5).…”
Section: Cork Simulationsupporting
confidence: 88%
“…The occurrence of the 6-hour time lag both in the magnetic field observations and the cork simulation is indicative of the passive nature of the magnetic field in supergranules and confirms the findings of Simon & Weiss (1989), Orozco Suárez et al (2012 and Roudier et al (2016). In our measurements and simulations, there is no sign of magnetic fields shaping the supergranular flows as proposed by Crouch et al (2007) or network field arising from random walks (Thibault et al 2012).…”
Section: Passive Magnetic Fieldsupporting
confidence: 85%
“…At any given time, there are far fewer supergranules than granules, therefore the resulting RV jitter associated with supergranules remains large. The supergranulation scale appears to Send offprint requests to: N. Meunier be strongly related to the large-scale dynamics of granules (e.g., Rieutord et al 2000;Roudier et al 2016). Furthermore, both granulation and supergranulation are expected to exhibit some power at low frequency, as suggested by the shape of the power spectrum proposed by Harvey (1984).…”
Section: Introductionmentioning
confidence: 99%
“…The flows in the photosphere can be observed either directly from Dopplergrams (e.g., Hathaway et al 2000), which provide estimates of the line-of-sight velocity component, or by the tracking of features, magnetic or otherwise, as they move across the surface (November & Simon 1988;Roudier et al 1999Roudier et al , 2012DeRosa & Toomre 2004;Meunier et al 2007b). The horizontal size of a supergranule can range between 20 and 60 Mm, with a typical size around 35 Mm (Hathaway et al 2000(Hathaway et al , 2002Del Moro et al 2004;DeRosa & Toomre 2004;Hirzberger et al 2008;Rieutord et al 2008).…”
Section: Introductionmentioning
confidence: 99%